Development of a virtual power plant using demand response management - Ooi, Yan Ning (2016)
The increase of distributed generation installation in the main grid is transforming the electrical power generation from centralized system to decentralized system. The aggregation control of several distributed generators forms the fundamental of VPP. This report introduces the concept of VPP and the demand response management system that is incorporated to the operation of VPP. Besides, a VPP is developed with the focus on its droop controller that performs external control for power sharing among a few distributed generators. The model is designed and simulated such that load shedding as a part of the demand response management system is performed during the simulation. The theory and simulation design architecture are presented in the report.